2014
DOI: 10.1371/journal.pone.0098656
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Macrophage Migration Inhibitory Factor Exposure Induces Mesenchymal Epithelial Transition and Promotes Gastric and Colon Cancers

Abstract: Macrophage Migration Inhibitory Factor (MIF) is an inflammatory cytokine that is highly produced in gastrointestinal cancers. Since chronic inflammation is a risk factor for tumorigenesis in these cancers, in this study, the role of MIF in pro-tumorigenic events was examined. MIF and its receptor, CD74, were examined in gastric and colon tumors and found to be increased in most tumors with significantly higher expression in tumors from patients with lymph node metastasis. MIF was also found to be highly produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Migration inhibitory factor is an inflammatory cytokine that is produced at high levels in the gastrointestinal tract during inflammatory disease and has been implicated in gastric and colon carcinogenesis . Expression of MIF has also been detected in human corneal basal epithelial cells and endothelial cells as well as in the iris, ciliary body, and retina, suggesting that MIF might play an important role in inflammation and immunity in the eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration inhibitory factor is an inflammatory cytokine that is produced at high levels in the gastrointestinal tract during inflammatory disease and has been implicated in gastric and colon carcinogenesis . Expression of MIF has also been detected in human corneal basal epithelial cells and endothelial cells as well as in the iris, ciliary body, and retina, suggesting that MIF might play an important role in inflammation and immunity in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Migration inhibitory factor is an inflammatory cytokine that is produced at high levels in the gastrointestinal tract during inflammatory disease and has been implicated in gastric and colon carcinogenesis. 32…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF) is a ubiquitously expressed, pleiotropic, pro-inflammatory cytokine that is part of the innate immune response to a wide range of infectious and inflammatory diseases, and can aggravate disease pathology [12, 13]. MIF promotes production and release of inflammatory mediators [for example, tumor necrosis factor alpha, TNFα; interferon-gamma, IFN-γ; interleukin (IL)-1β, IL-2, IL-6, and IL-8], inhibits macrophage and neutrophil apoptosis, and counteracts the anti-inflammatory functions of glucocorticoids [1417].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data have shown that CD74 protein is upregulated in cancer cells, indicating its role in carcinogenesis and angiogenesis [63][64][65][66]. Moreover, it is well known that there is a close link between chronic inflammation and malignancies, which could be initiated by recruitment of inflammatory cells and production of inflammatory mediators.…”
Section: Cd74mentioning
confidence: 99%